Pembangunan Ekonomi Masyarakat Berbasis Community Empowerment Pada Wisata Taman Siti Sundari di Kecamatan Senduro Lumajang - Nita Andriani (Fakultas Dakwah IAIN Jember, 2020)
The economic downturn in Indonesia after Covid-19 pandemic can be perceived generally from Indonesia’s current situation in the second quarter in which a 5.3% decline is apparent. The decline has risen by 0.3% from 5% since the last 10 years. Naturally, the economic decline also occurred in Lumajang district where the economic growth reached up to 5.02% in 2018, then decreased to 4.77% in 2019. One of the ways that LMDH is doing to improve the economy of Senduro people in Lumajang is by empowering the community. Seeing the potential natural resources that Burno Village has, the LMDH and the local community are working together with Perhutani to create a Taman Siti Sundari attraction. The purpose of this study was to determine the concept of community economic empowerment carried out by LMDH in order to improve the economic welfare of the community around Taman Siti Sundari. The current study also aims at knowing the size of the economic growth amongst the community that resulted from the LMDH empowerment program in Taman Siti Sundari. The researchers employed descriptive qualitative for the research method. The primary data was taken from the interview data from the interviewees. Triangulation method was also employed to validate the data. The result showed that the concept of community economic empowerment carried out by LMDH was in accordance with Ibn Khaldun's theory of economic development. LMDH carried out the task by emphasizing the important role in the concept of development such as being ar-rijal (community), LMDH as a community that manages, having al-imarah (development) of Taman Siti Sundari, and having natural resources which become al-mal (wealth). For the amount of income from this attraction, the community is given entrepreneurial land and profitable job since the parking income alone gains IDR 51,000,000 / month.